Bellezza della coralità, bellezza di una casa (Materiali di Estetica. Terza serie, 2024)
The author delves into themes of beauty in incompleteness, communal belonging, and the warmth of shared spaces, connecting these reflections to wider existential and spiritual questions
Keywords: homily; rchitectural metaphor; communal spirituality; existential themes.